2009
DOI: 10.1002/lary.20553
|View full text |Cite
|
Sign up to set email alerts
|

A new treatment option for laryngeal sensory neuropathy

Abstract: Pregabalin therapy appears to be an effective treatment option for laryngeal sensory neuropathy. Future prospective studies are needed to compare outcomes between pregabalin and other medications as treatments for LSN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(90 citation statements)
references
References 16 publications
0
87
2
1
Order By: Relevance
“…However, gabapentin treatment effect had not reached a plateau by 8 weeks suggesting that longer-term treatment may be required for some patients. A risk versus benefits analysis would need to be done for individual patients.Halum et al, 2009 [102]Retrospective chart review of consecutive patients prescribed pregabalin for symptoms of LSN including CC.5 Pregabalin 75–150 mg bidPre- and posttreatment questionnaires asking patients to rate symptoms on a scale from 0 to 53 of 5 improved cough severity None of the patients developed drug tolerance effects over time.Sedation in 4 (80%), of whom half tolerated, half discontinuedmedicationRetrospective chart review. No objective measures of improvement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, gabapentin treatment effect had not reached a plateau by 8 weeks suggesting that longer-term treatment may be required for some patients. A risk versus benefits analysis would need to be done for individual patients.Halum et al, 2009 [102]Retrospective chart review of consecutive patients prescribed pregabalin for symptoms of LSN including CC.5 Pregabalin 75–150 mg bidPre- and posttreatment questionnaires asking patients to rate symptoms on a scale from 0 to 53 of 5 improved cough severity None of the patients developed drug tolerance effects over time.Sedation in 4 (80%), of whom half tolerated, half discontinuedmedicationRetrospective chart review. No objective measures of improvement.…”
Section: Resultsmentioning
confidence: 99%
“…It acts on central nervous system calcium channels, leading to decreased release of neurotransmitters such as glutamate, noradrenaline, and substance P. Halum et al [102] showed that pregabalin was effective in the treatment of a small number of patients with laryngeal sensory neuropathy. In 2016, Vertigan et al [90] compared a combination treatment of pregabalin (PREG) and SPT to a matching placebo medication (PLAC) and SPT for patients with refractory CC (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7][8]10 It is currently considered that, vagal neuropathy predisposes the laryngeal mucosa to be more sensitive to even low-intensity stimuli, such as laughing, speaking, smoking, and so forth, that triggers the afferent pathway of cough reflex arc persistently. Vagal neuropathy may involve either the sensorial or motor branches of the vagal nerve after preceding viral URI.…”
Section: Discussionmentioning
confidence: 99%
“…Because ''irritable larynx syndrome'' was first described in 1999, many of titles including sensory neuropathic cough, laryngeal sensory neuropathy, and postviral vagal neuropathy (PVVN) have been used to define the same clinical setting throughout the years. [4][5][6] PVVN is associated with persisting symptoms after viral upper respiratory infection in which neuropathy may affect the sensory branches of the vagus nerve, resulting in lowered threshold for nerve firing, which triggers a throat tickle and chronic cough. Neuropathy may involve the motor branches as well, as evidenced by vocal fold paralysis or paresis.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the involvement of central neural mechanisms in chronic cough can be elicted from a history of abnormal laryngeal sensations (laryngeal paraesthesia), cough hypersensitivity to nontussive stimuli (termed allotussia), a heightened response to tussive stimuli (hypertussia), and a response to centrally acting medications such as gabapentin [22], pregabalin [23], morphine [24], and amitryptyline [18,25].…”
Section: Central Sensitivity In Refractory Coughmentioning
confidence: 99%